Isolation, characterization and pathogenicity of epizootic ulcerative syndrome-related Aphanomyces toward an improved diagnostic technique - Afzali, Seyedeh Fatemeh (2014)
Epizootic ulcerative syndrome (EUS) is a seasonal and severely damaging disease in wild and farmed freshwater and estuarine fishes. The disease has been spread through countries of the Asia-Pacific region with dire consequences to the fish resources and livelihood of fishermen. It has been a major concern almost all over the world since 1972. Epizootic ulcerative syndrome is a disease which manifested with severe skin and muscle ulceration and caused heavy mortalities in freshwater fishes. The aquatic fungus, Aphanomyces invadans, which belongs to the family Saprolegniacea, has been identified as the causative agent of EUS. Up to date no effective prophylactic measures and no protective vaccines are available against this disease. If scientific development could not solve this microbiological problem, it is likely to impact a noticeable negative income in the future especially for fish farmers who rely on wild-caught fish for income. Thus this study aimed to (i) isolate and identify Aphanomyces spp. from Malaysian water bodies and fish farms, (ii) determine the pathogenicity of A. invadans on the Malaysian local fish, and (iii) improve a molecular technique (PCR) for a rapid and reliable detection of EUS infection. Four hundred sixty one water and 235 fish were sampled from different water bodies and fish farms in Selangor state of Malaysia from February 2011 until February 2013. Oomycete fungi were isolated by applying bait methods using hempseed and corn, and identified according to their hyphae, sporangium and oogonium morphological characteristics. Through experimentally infection studies, Snakehead fish (Channa striata) (positive control), Moonlight gourami (Trichopodus microlepis), Snakeskin gourami (Trichopodus pectoralis), Koi carp (Cyprinus carpio carpio), Broadhead catfish (Clarias macrocephalus), Goldfish (Carasius auratus auratus), Climbing perch (Anabas testudineus) and Tilapia (Oreochromis niloticus) (negative control) were challenged by intramuscular injection and cohabitation using zoospores of a reference A. invadans NJM9701 (isolated from naturally infected Ayu by Dr. Hatai in Japan, 1997). Aphanomyces invadans was able to be re-isolated from experimentally infected Moonlight gourami and Koch’s postulates were fulfilled to confirm the exact source of infection in this study. Aphanomyces invadans DNA were extracted from experimentally infected fish skin and muscle at different days of post inoculation and were detected by the PCR method by using the primer set 1APM 1 F, 1APM 6R which were commercially available in the market. From 73 water samples which were positive for fungi, 31 isolates were identified as Saprolegnia spp., 27 isolates as Achlya spp., 12 isolates as Aphanomyces spp., and three isolates as Allomyces spp. Among of 235 naturally infected fish, 62 samples were positive for fungi infection which identified as Saprolegnia (34 samples) and Achlya (28 samples). Snakeheads experimentally infected with local isolates of Aphanomyces did not show any EUS typical clinical signs and no mortalities were observed in any group during observation period, which indicated that the local isolates of Aphanomyces spp., were of saprophytic strains. Snakehead, Gouramy, Koi carp, Broadhead catfish, Goldfish and Climbing perch injected with zoospores from reference strain developed lesions that were grossly and histopathologically identical to those observed in naturally infected fish and 100% mortalities were observed. Histopathological studies showed severe cellular inflammatory infiltration, granulomatous formations and presence of invasive fungal hyphae in zoospores injected fish skins and muscles. The DNA extraction protocol used in this study was successful in isolating A. invadans genomic DNA from fish muscles and pure cultured fungus, and the improved PCR assay also was able to detect the presence of A. invadans DNA in experimentally infected fish skin and muscle from day one post inoculation. This study was the first research conducted on freshwater aquatic fungi in Malaysia and successfully showed the presence of Aphanomyces spp., and other oomycete fungi in Malaysian water bodies. It is found that Malaysian Moonlight gourami, Snakeskin gourami, Koi carp and Broadhead catfish are highly susceptible while Goldfish and Climbing perch are moderately susceptible to infection by A. invadans via intramuscular injection. The infection is also capable of being transferred to healthy susceptible fish through the water column. It is concluded that by applying PCR assay A. invadans could be detected in clinical samples in very early stages of disease. Because of the presence of Aphanomyces spp., and EUS-susceptible fish in freshwater resources of Malaysia, there is potential risk of EUS outbreak in the region which thus must be avoided by good prophylactic measures and rigid farm biosecurity.